Theoretical Modeling of the Diffuse Emission of Gamma Rays from Extreme Regions of Star Formation: The Case of ARP 220 - Torres, Diego F (The Astrophysical journal, 2004)
Our current understanding of ultraluminous infrared galaxies suggests that they are recent galaxy mergers in which much of the gas in the former spiral disks, particularly that located at distances less than 5 kpc from each of the premerger nuclei, has fallen into a common center, triggering a huge starburst phenomenon. This large nuclear concentration of molecular gas has been detected by many groups, and estimates of molecular mass and density have been made. Not surprisingly, these estimates were found to be orders of magnitude larger than the corresponding values found in our Galaxy. In this paper, a self-consistent model of the high-energy emission of the superstarburst galaxy Arp 220 is presented. The model also provides an estimate of the radio emission from each of the components of the central region of the galaxy (western and eastern extreme starbursts and molecular disk). The predicted radio spectrum is found as a result of the synchrotron and free-free emission and absorption of the primary and secondary steady population of electrons and positrons. The latter is the output of charged pion decay and knock-on leptonic production, subject to a full set of losses in the interstellar medium. The resulting radio spectrum is in agreement with subarcsecond radio observations, which is what allows us to estimate the magnetic field. In addition, the FIR emission is modeled with dust emissivity, and the computed FIR photon density is used as a target for inverse Compton process as well as to give an account of losses in the gamma -ray escape. Bremsstrahlung emission and neutral pion decay are also computed, and the gamma -ray spectrum is finally predicted. Future possible observations with GLAST and the ground-based Cerenkov telescopes are discussed.